THE IMPACT OF INTELLECTUAL CAPITAL ON FIRM VALUE AND FINANCIAL PERFORMANCE AS INTERVENING VARIABLES IN MANUFACTURING COMPANIES IN THE BASIC AND CHEMICAL INDUSTRIAL SECTORS ON INDONESIA STOCK EXCHANGE YEAR 2012-2020 - Marpaung, Pertiwi; Br Bukit, Rina; Absah, Yeni (CV. Radja Publika, 2023)
This study aims to determine the effect of intellectual capital on firm value and financial performance as an intervening variable. In addition, this study also aims to determine whether financial performance can be used as an intervening variable in this research model.This type of research is quantitative research. The population in this study are manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange. Samples were taken using a non-probability sampling technique with purposive sampling method, so that 13 companies were selected with 117 total observations. The data analysis technique used path analysis technique.The results of the analysis show that VACA and VAHU have no significant effect on financial performance while STVA has a significant effect on financial performance. VACA and VAHU have a significant effect on firm value while STVA has no significant effect. The financial performance variable cannot mediate the effect of VACA and VAHU on firm value while it can mediate the effect of STVA on firm value.